Error Analysis for Students of the Department of Arabic Language Teaching/تحليل الأخطاء لطلبة قسم تعليم اللغة العربية - Wijaya, Mualim (JURNAL IJ-ATL, 2017)
The aim of this research is to find out the mistakes of the students of the Department of Arabic Language Teaching at the New Islamic University of Paiton and to find out the reasons for their mistakes in verbal errors and then provide the corresponding solutions. The methodology of the research is the quantitative approach to the analytical description using the non-random input (Random Non Sample). Research tools are documents and observation. The research community is the students of the Department of Language Education at Nurul Jadid University for the academic year 2017-2018, and the number of students is 102 students. The results of the research showed that the mistakes of the words of the students of the Department of Arabic Language mistakes verbal mistakes are synthetic as you?, and semantic as I first, and the basic as I want to go. The causes of verbal errors are the impact on the mother tongue, the narrow curriculum, the quality of teaching, the lack of Arabic language and the negation of the Arabic language environment. The appropriate solutions for verbal errors are that the teacher should be a good linguistic character at every occasion, expand the educational quota and provide the means specified and the Arab environment.يهدف هذا البحث إلى معرفة الأخطاء الكلامية لطلبة قسم تعليم اللغة العربية بجامعة النور الجديد الإسلامية بيطان ومعرفة أسباب وقوعهم في  الأخطاء الكلامية ثم تقديم الحلول المطابق لها. ومنهجية البحث هو المدخل الكيفي الوصف التحليلي باستخدام المدخل غير العشوائي (Random Non Sampel). وأما أدوات البحث فهي الوثائق والملاحظة فالمقابلة. ومجتمع البحث هو طلبة قسم تعليم اللغة بجامعة النور الجديد الإسلامية للعام الدراسي 2017-2018 مـ، وعدد الطلبة فيها 102 طالبة وطالبة. وقد دلت نتائج البحث على أن الأخطاء الكلامية لطلبة قسم تعليم اللغة العربية الاخطاء الكلامية هي الأخطاء التركيبية كأنت من؟، والدلالية كأرجع أولا، والقواعدية كأريد أن أذهبُ. وأسباب الأخطاء الكلامية هي التأثر باللغة الأم والمنهج الدراسي الضيق ونوعية التدريس وعدم الأسوة اللغوية العربية ونفي البيئة اللغوية العربية. والحلول المناسبة للأخطاء الكلامية هي ينبغي أن يكون المعلم أسوة لغوية حسنة في كل مناسبة ويوسع الحصة التعليمية ويوفر الوسائل المعينة ويكوّن البيئة العربية.